Protein Corona Prevents TiO2 Phototoxicity - Garvas, Maja; Testen, Anze; Umek, Polona; Gloter, Alexandre; Koklic, Tilen; Strancar, Janez (PLOS ONE, 2015)
Background & Aim TiO2 nanoparticles have generally low toxicity in the in vitro systems although some toxicity is expected to originate in the TiO2-associated photo-generated radical production, which can however be modulated by the radical trapping ability of the serum proteins. To explore the role of serum proteins in the phototoxicity of the TiO2 nanoparticles we measure viability of the exposed cells depending on the nanoparticle and serum protein concentrations. Methods & Results Fluorescence and spin trapping EPR spectroscopy reveal that the ratio between the nanoparticle and protein concentrations determines the amount of the nanoparticles’ surface which is not covered by the serum proteins and is proportional to the amount of photo-induced radicals. Phototoxicity thus becomes substantial only at the protein concentration being too low to completely coat the nanotubes’ surface. Conclusion These results imply that TiO2 nanoparticles should be applied with ligands such as proteins when phototoxic effects are not desired - for example in cosmetics industry. On the other hand, the nanoparticles should be used in serum free medium or any other ligand free medium, when phototoxic effects are desired – as for efficient photodynamic cancer therapy.